2022
DOI: 10.3847/1538-4365/ac374a
|View full text |Cite
|
Sign up to set email alerts
|

A Fresh Look at AGB Stars in Galactic Open Clusters with Gaia: Impact on Stellar Models and the Initial–Final Mass Relation

Abstract: Benefiting from the Gaia second and early third releases of photometric and astrometric data, we examine the population of asymptotic giant branch (AGB) stars that appear in the fields of intermediate-age and young open star clusters. We identify 49 AGB star candidates, brighter than the tip of the red giant branch, with a good to high cluster membership probability. Among them, we find 19 TP-AGB stars with known spectral type: 4 M stars, 3 MS/S stars, and 12 C stars. By combining observations, stellar models,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 204 publications
0
16
0
Order By: Relevance
“…Using the same relation, we can claim that a fraction of the AGB stars that polluted our sample of Ba stars were more massive than the expected 3 M limit, since we found that several WDs have masses around or higher than 0.8 M . This is the case even taking into account the kink that Marigo et al (2020Marigo et al ( , 2022 find for WDs of about 0.70 -0.75 M with carbon AGB progenitors. Most IFMRs (e.g.…”
Section: A Comment On Nucleosynthesis Predictionsmentioning
confidence: 89%
“…Using the same relation, we can claim that a fraction of the AGB stars that polluted our sample of Ba stars were more massive than the expected 3 M limit, since we found that several WDs have masses around or higher than 0.8 M . This is the case even taking into account the kink that Marigo et al (2020Marigo et al ( , 2022 find for WDs of about 0.70 -0.75 M with carbon AGB progenitors. Most IFMRs (e.g.…”
Section: A Comment On Nucleosynthesis Predictionsmentioning
confidence: 89%
“…1. The faint companion could be a 1.3 M WD, implying an AGB progenitor of a rather high mass, of the order of 6 M (Marigo et al 2022). However, massive AGB stars are not A new exploration of the nucleosynthesis parameter space could add to this discussion.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
“…Grady et al 2020). A limited number of Mira variables in clusters also validate the period-age connection although confident assignment of membership has only been possible recently with Gaia data (Grady et al 2019;Marigo et al 2022). Although the period-age relation has been approximately calibrated empirically (Feast & Whitelock 2000b), relatively few theoretical models reproducing the behaviour exist (Wyatt & Cahn 1983;Eggen 1998;Trabucchi & Mowlavi 2022) and the lack of detailed reproduction of the period-luminosity relations of fundamental mode pulsation from theoretical models suggests the period-age relations still have some associated uncertainty and there is a need for accurate data-driven calibrations.…”
Section: Introductionmentioning
confidence: 90%